Optimal. Leaf size=14 \[ \frac {2 x}{3-e^{2 x}} \]
________________________________________________________________________________________
Rubi [B] time = 0.32, antiderivative size = 90, normalized size of antiderivative = 6.43, number of steps used = 17, number of rules used = 12, integrand size = 30, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.400, Rules used = {6688, 6742, 2185, 2184, 2190, 2279, 2391, 2191, 2282, 36, 31, 29} \begin {gather*} \frac {2 x^2}{3}-\frac {1}{6} (1-2 x)^2+\frac {2 x}{3-e^{2 x}}-\frac {2 x}{3}-\frac {1}{3} (1-2 x) \log \left (1-\frac {e^{2 x}}{3}\right )+\frac {1}{3} \log \left (3-e^{2 x}\right )-\frac {2}{3} x \log \left (1-\frac {e^{2 x}}{3}\right ) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 29
Rule 31
Rule 36
Rule 2184
Rule 2185
Rule 2190
Rule 2191
Rule 2279
Rule 2282
Rule 2391
Rule 6688
Rule 6742
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {6+e^{2 x} (-2+4 x)}{\left (3-e^{2 x}\right )^2} \, dx\\ &=\int \left (\frac {12 x}{\left (-3+e^{2 x}\right )^2}+\frac {2 (-1+2 x)}{-3+e^{2 x}}\right ) \, dx\\ &=2 \int \frac {-1+2 x}{-3+e^{2 x}} \, dx+12 \int \frac {x}{\left (-3+e^{2 x}\right )^2} \, dx\\ &=-\frac {1}{6} (1-2 x)^2+\frac {2}{3} \int \frac {e^{2 x} (-1+2 x)}{-3+e^{2 x}} \, dx+4 \int \frac {e^{2 x} x}{\left (-3+e^{2 x}\right )^2} \, dx-4 \int \frac {x}{-3+e^{2 x}} \, dx\\ &=-\frac {1}{6} (1-2 x)^2+\frac {2 x}{3-e^{2 x}}+\frac {2 x^2}{3}-\frac {1}{3} (1-2 x) \log \left (1-\frac {e^{2 x}}{3}\right )-\frac {2}{3} \int \log \left (1-\frac {e^{2 x}}{3}\right ) \, dx-\frac {4}{3} \int \frac {e^{2 x} x}{-3+e^{2 x}} \, dx+2 \int \frac {1}{-3+e^{2 x}} \, dx\\ &=-\frac {1}{6} (1-2 x)^2+\frac {2 x}{3-e^{2 x}}+\frac {2 x^2}{3}-\frac {1}{3} (1-2 x) \log \left (1-\frac {e^{2 x}}{3}\right )-\frac {2}{3} x \log \left (1-\frac {e^{2 x}}{3}\right )-\frac {1}{3} \operatorname {Subst}\left (\int \frac {\log \left (1-\frac {x}{3}\right )}{x} \, dx,x,e^{2 x}\right )+\frac {2}{3} \int \log \left (1-\frac {e^{2 x}}{3}\right ) \, dx+\operatorname {Subst}\left (\int \frac {1}{(-3+x) x} \, dx,x,e^{2 x}\right )\\ &=-\frac {1}{6} (1-2 x)^2+\frac {2 x}{3-e^{2 x}}+\frac {2 x^2}{3}-\frac {1}{3} (1-2 x) \log \left (1-\frac {e^{2 x}}{3}\right )-\frac {2}{3} x \log \left (1-\frac {e^{2 x}}{3}\right )+\frac {1}{3} \text {Li}_2\left (\frac {e^{2 x}}{3}\right )+\frac {1}{3} \operatorname {Subst}\left (\int \frac {1}{-3+x} \, dx,x,e^{2 x}\right )-\frac {1}{3} \operatorname {Subst}\left (\int \frac {1}{x} \, dx,x,e^{2 x}\right )+\frac {1}{3} \operatorname {Subst}\left (\int \frac {\log \left (1-\frac {x}{3}\right )}{x} \, dx,x,e^{2 x}\right )\\ &=-\frac {1}{6} (1-2 x)^2-\frac {2 x}{3}+\frac {2 x}{3-e^{2 x}}+\frac {2 x^2}{3}+\frac {1}{3} \log \left (3-e^{2 x}\right )-\frac {1}{3} (1-2 x) \log \left (1-\frac {e^{2 x}}{3}\right )-\frac {2}{3} x \log \left (1-\frac {e^{2 x}}{3}\right )\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.05, size = 12, normalized size = 0.86 \begin {gather*} -\frac {2 x}{-3+e^{2 x}} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.87, size = 11, normalized size = 0.79 \begin {gather*} -\frac {2 \, x}{e^{\left (2 \, x\right )} - 3} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.15, size = 11, normalized size = 0.79 \begin {gather*} -\frac {2 \, x}{e^{\left (2 \, x\right )} - 3} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.06, size = 12, normalized size = 0.86
method | result | size |
norman | \(-\frac {2 x}{{\mathrm e}^{2 x}-3}\) | \(12\) |
risch | \(-\frac {2 x}{{\mathrm e}^{2 x}-3}\) | \(12\) |
default | \(\frac {2 \ln \left ({\mathrm e}^{x}\right )}{3}-\frac {2 x \,{\mathrm e}^{2 x}}{3 \left ({\mathrm e}^{2 x}-3\right )}\) | \(22\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.38, size = 19, normalized size = 1.36 \begin {gather*} \frac {2}{3} \, x - \frac {2 \, x e^{\left (2 \, x\right )}}{3 \, {\left (e^{\left (2 \, x\right )} - 3\right )}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.13, size = 11, normalized size = 0.79 \begin {gather*} -\frac {2\,x}{{\mathrm {e}}^{2\,x}-3} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.09, size = 10, normalized size = 0.71 \begin {gather*} - \frac {2 x}{e^{2 x} - 3} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________